2018
DOI: 10.3346/jkms.2018.33.e81
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Standardization of Diagnostic Tests on the Prevalence of Diabetes Mellitus and Impaired Fasting Glucose

Abstract: BackgroundWithout standardization of medical laboratory's testing practices, there is an increase in false diagnoses when relying on test results. However, the effect of test standardization is difficult to assess numerically. This study's purpose is to quantify the effect of the standardization level of a laboratory on the prevalence of diabetes mellitus (DM) and impaired fasting glucose (IFG).MethodsLaboratories were classified into three levels: ‘highly-standardized laboratory,’ ‘basically-standardized labo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…Moreover, we found that the prevalence computed from hospital-based studies (9.0%) was higher from populationbased studies (6.9%). This might be attributed to the difference between the diagnostic tools and standards used [32]. Also, people who come to hospital with a health condition might already have some major risk factors associated with developing DM.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, we found that the prevalence computed from hospital-based studies (9.0%) was higher from populationbased studies (6.9%). This might be attributed to the difference between the diagnostic tools and standards used [32]. Also, people who come to hospital with a health condition might already have some major risk factors associated with developing DM.…”
Section: Discussionmentioning
confidence: 99%
“…There are several other studies that indicated the prevalence of diabetes is increasing, passing the time [40,41]. These are not only related to the increasing trend of physical inactivity and consumption of unhealthy diet but also progression in diagnostic techniques as well as effective strategies for detection and follow-up people with dysglycemia [42].…”
Section: Discussionmentioning
confidence: 99%